Synthesis and Antibacterial Screening of 2-(p-Acetamidophenoxy)-1-aryl-3-phenyl-3-oxoprop- 1-ene(substituted)pyrazoles - SREEDHAR, CHANDANAM; BAJJI, A.C.; VRUSHABENDRA SWAMY, B.M. (Asian Journal of Chemistry, 2010)
A new series of substituted pyrazoles as 2-(p-acetamidophenoxy)- 1-aryl-3-phenyl-3-oxo-prop-1-ene pyrazoles was synthesized (4a-e). The compounds were evaluated for antibacterial activity using B. substilis, S. aureus, P. vulgareus and E. coli. All the compounds exhibited moderate antibacterial activity.